Irish Wave Data—Rogues, Analysis and Continuity - Méabh Nic Guidhir; Donal Kennedy; Alan Berry; Barry Christy; Colm Clancy; Columba Creamer; Guy Westbrook; Sarah Gallagher (Journal of Marine Science and Engineering, 2022)
The Marine Institute of Ireland operates a network of weather buoys around Ireland. A wave of 32.3 m height (crest–trough) was recorded by one of these buoys, the M6 buoy, off the coast of Ireland in October 2020. In this paper, the technological evolution of this network is explored, with a particular emphasis on this extremely high wave. Raw data and bulk parameters collected during the event are presented, and the wider met-ocean context is outlined. In addition, wave data across the buoy deployment period from dual wave sensors installed on the buoy are analysed. Differences in calculation methods are discussed, rogue incidence rates are calculated, and the sensors are found to be generally in good agreement for key sea state parameters. Considerations specific to this network of buoys are described, including recent advances in technology that may affect continuity of historic records. Wave data from the buoys are found to be robust; the importance of keeping technological changes in mind and using the full raw dataset for analysis purposes are highlighted.